On-pump coronary artery bypass surgery in vascular Ehlers-Danlos syndrome. (24th November 2014) - Kelly, R P; Horne, S G; Molinari, M; Wood, J
Abstract : A 58-year-old woman with vascular Ehlers-Danlos syndrome (EDS; type IV) presented to a Canadian tertiary care emergency department with a non-ST elevation myocardial infarction. The patient failed medical therapy and after careful consideration of the options, elected to undergo urgent coronary artery bypass (CABG) surgery. To the best of our knowledge, this is the first reported case of a successful on-pump CABG surgery in a patient with vascular EDS.